(untitled) (Jalalabad Medical Journal, 2026)
Goldenhar syndrome is a rare congenital condition characterised by a range of anomalies, including ear malformations, hemifacial microsomia, epibulbardermoids, vertebral anomalies, and potential internal organ defects. This syndrome arises from maldevelopment of the first and second branchial arches during early embryonic stages. Here we report a case of Goldenhar syndrome with congenital heart disease, bilateral microtia, and hemifacial microsomia. Jalalabad Med J 2025; 22 (1): 37-39.